2008
DOI: 10.3136/fstr.14.62
|View full text |Cite
|
Sign up to set email alerts
|

Functional Component Contents in Mature Leaves, Young Shoots, and Adventitious Shoots of Japanese Persimmon 'Saijo'

Abstract: The mature leaves of Japanese 'Saijo' persimmon (Diospyros kaki Thunb.) are consumed as ingredients in health foods and teas. Levels of ascorbic acid and polyphenols were compared between the mature leaf (M-leaf), young shoot (T-shoot; cultured by water-soaking twigs grown the previous year) and adventitious shoot (A-shoot; obtained from orchard trees). The level of total ascorbic acid (T-AsA) was highest in M-leaves, and though the levels of polyphenols were high in M-leaf and A-shoot, they were remarkably lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…No additional peaks, which are possible to be characterized, were detected by the absorptions at 280 and 254 nm. Compared with the retention time and the m / z of the standard compounds, quercetin-3- O -β- d -galactopyranoside (hyperoside, peak A), quercetin-3- O -β- d -glucopyranoside (isoquercitrin, peak B), kaempferol-3- O -β- d -galactopyranoside (trifolin, peak D), and kaempferol-3- O -β- d -glucopyranoside (astragalin, peak E) were identified, which is consistent with previous studies. ,, To identify peaks C, F, and G, 1 H and 13 C 1D NMR spectra and 1 H– 13 C HSQC, 1 H– 13 C HMBC, and 1 H– 1 H DQF-COSY 2D NMR spectra were measured, following the confirmation of the molecular weights by the MALDI-TOF MS spectra. These analyses showed that the C, F, and G peaks were quercetin-3- O -(2′′- O -galloyl-β- d -glucopyranoside) (QOG), kaempferol-3- O -(2′′- O -galloyl-β- d -glucopyranoside) (KOG), and cyanidin-3- O -β- d -glucopyranoside (chrysontemin), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…No additional peaks, which are possible to be characterized, were detected by the absorptions at 280 and 254 nm. Compared with the retention time and the m / z of the standard compounds, quercetin-3- O -β- d -galactopyranoside (hyperoside, peak A), quercetin-3- O -β- d -glucopyranoside (isoquercitrin, peak B), kaempferol-3- O -β- d -galactopyranoside (trifolin, peak D), and kaempferol-3- O -β- d -glucopyranoside (astragalin, peak E) were identified, which is consistent with previous studies. ,, To identify peaks C, F, and G, 1 H and 13 C 1D NMR spectra and 1 H– 13 C HSQC, 1 H– 13 C HMBC, and 1 H– 1 H DQF-COSY 2D NMR spectra were measured, following the confirmation of the molecular weights by the MALDI-TOF MS spectra. These analyses showed that the C, F, and G peaks were quercetin-3- O -(2′′- O -galloyl-β- d -glucopyranoside) (QOG), kaempferol-3- O -(2′′- O -galloyl-β- d -glucopyranoside) (KOG), and cyanidin-3- O -β- d -glucopyranoside (chrysontemin), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…There are many reports on the antioxidant activity of the fruit, leaf, and peel of persimmons (Fukai et al, 2009;Lee et al, 2008;Tsurunaga et al, 2008;Jung et al, 2005). Studies of the antioxidant activity of persimmon seeds have been carried out (Ahn et al, 2002;Cantrell et al, 2003;Jang et al, 2010); however, few studies have compared the functional activity of seeds of different persimmon cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The leaves of D. kaki, which is a traditional Chinese medicinal, have been used for years for the treatment of stroke and the syndrome of apoplexy in clinics in China to improve the effect of ischemia stroke [3,4] and utilized as a hypotensive drug in Japanese traditional medicine. [5] The fresh or dry leaves of D. kaki are also infused with hot (rather than boiled) water and have traditionally been drunk as green tea [6][7][8] or a natural food additive [9,10] for healthcare in southeast Asia, being able to improve the antioxidant activities in vivo, inhibit lipid peroxide, [11] lower hepatic cholesterol, [9] and having also become increasingly popular as a healthy food.…”
Section: Introductionmentioning
confidence: 99%